Use of rilpivirine in HIV-1-infected individuals in routine clinical practice from 2012 to 2017 in France. (5th December 2020) - Potard, Valérie; Gallien, Sebastien; Canestri, Ana; Costagliola, Dominique; ,
Abstract: Objectives: We assessed virological outcomes of rilpivirine use in France from 2012 to 2017, in three groups of people living with HIV (PLHIV): (i) antiretroviral (ARV)-naive PLHIV; (ii) ARV-experienced PLHIV switching to rilpivirine while failing therapy; and (iii) ARV-experienced PLHIV switching to rilpivirine while virologically controlled. Methods: Virological success (VS) was defined as a plasma HIV-1 viral load (VL) <50 copies/mL and virological failure (VF) as two consecutive VL >50 copies/mL or one VL >50 copies/mL followed by a treatment switch prior to the next VL measurement. The cumulative incidence of VS was assessed considering rilpivirine discontinuation, loss to follow-up and death as competing risks, while estimates of cumulative incidence of VF accounted for loss to follow-up and death. Results: Among the 2166 ARV-naive PLHIV initiating rilpivirine, the 4 year cumulative incidence of VS was 91.0% and was associated with baseline VL. Among the 2125 ARV-experienced PLHIV switching to rilpivirine while failing therapy, the 4 year cumulative incidence of VS was 82.5% and was associated with lower VL, higher CD4 and less than three prior ARVs. Among the 11 828 ARV-experienced PLHIV switching to rilpivirine while virologically controlled, the 4 year cumulative incidence of VF was 9.6%. The risk of VF was lower among MSM, for PLHIV with CD4 ≥ 500 cell/mm 3, without a prior AIDS event, or with a longer VL suppression at baseline. Conclusions: Rilpivirine-containing regimens yielded high rates of viral suppression in most participants, while it was ineffective when used outside the marketing authorization in naive participants.